Monitoring of airborne organic compounds using lichen xanthoria parietina in regions of intensive livestock breeding - ÇOBANOĞLU, GÜLŞAH (My University, 2023)
Lichens are known to be sensitive to air pollution and are rich in sensitive species in areas with high air quality. Bioindicator lichen species are organisms that inform about atmospheric elements and compounds. It is noteworthy that the epiphytic lichen Xanthoria parietina, known as a nitrogen-loving species, is much more common in areas where animal husbandry is intense in Balıkesir province in Turkey. Small cattle breeding (sheep and goats) and cattle breeding (dairy cattle) are carried out intensively in this region and there are integrated meat facilities and dairy farms depending on animal husbandry. Therefore, especially ammonia, sulfur compounds, methane, and carbon dioxide, which are nitrogenous compounds originating from livestock, are present in the air intensively. In this study, it was aimed to detect airborne compounds accumulated in lichens with FTIR spectroscopy, which is used in the determination of many substances such as organic, inorganic, plastics, and polymers. For this purpose, lichen samples collected from the region were analyzed and air quality was correlated with the lichen monitoring method. In addition, the relationship between livestock and lichen composition in the region has been examined and the indicator roles of lichens on this issue were evaluated
Keywords: Lichen; Air Quality; FTIR Spectroscopy; Bioindicator; Breeding